Nas ondas da pororoca: repercussões sócio-espaciais da atividade turística no município de São Domingos do Capim (Pará) - SOUZA, Jorge Alex de Almeida (Universidade Federal do Pará, 2011)
The current article establishes delibertions about the touristy activity repercussion at Amazonian municipality, the municipality of São Domingos do Capim (Pará). During his development on the local space, the tourism, exploring the image et a Amazonian that gather adventures, mythos and legends, through of the pororocas phenomenon have been provocaded sociospatial repercussions at the city on the cotidians pratices point of view. Understanding that tourism active at a city of Pará s interior, with hybrid caracteristcs of space (riparian and urban), restructures temporalities and territorialities diverses, defining again in consequence, forms and content of local space. In the present analysis, one searchs to evidence the lived space local and its relation with the intensification of the tourist activity in the City, in particular the ribeirinha everyday dimension. For all, the research was used of the space dialectic (LEFEBVRE, 1981) as reflection ahead of the production of the space, in view of the involved agents. In the field work, five essential categories in the production of the space had been interviewed: local population, tourist, sponsors, government of the State of Pará and local public power. The results had disclosed to have conceptions and related different scienters to the insertion of the tourist activity in the city, as well its planning and its programming had conflicted with the ribeirinho lived dimension.